Designing Horror-Themed Animated Content Titled "What Awaits in The Darkness" to Introduce Ruhilism Studio's Style - Lintang Ruhil Hidayah; Hutomo Setia Budi (Jurnal Vicidi, 2023)
Ruhilism is an animation studio that presents horror and thriller-themed animated content as entertainment for fans of both genres. Ruhilism is unique in its creepy and eerie art style. However, Ruhilism does not have a portfolio to show its uniqueness in order to be recognized by the public. The purpose of this design is to show the uniqueness of Ruhilism Studio's distinctive style to the public through a portfolio in the form of animated content uploaded on Instagram and Youtube media. The design method used is a combination of qualitative and quantitative, namely interviews and surveys conducted online. The results of the design are in the form of horror and thriller-themed animated content uploaded on the Ruhilism Youtube Channel and Ruhilism Instagram as supporting media.